Towards understanding the mechanism of action of antibacterial N-alkyl-3-hydroxypyridinium salts: Biological activities, molecular modeling and QSAR studies - Dolezal, Rafael; Soukup, Ondrej; Malinak, David; Savedra, Ranylson M L; Marek, Jan; Dolezalova, Marie; Pasdiorova, Marketa; Salajkova, Sarka; Korabecny, Jan; Honegr, Jan; Ramalho, Teodorico C; Kuca, Kamil (European journal of medicinal chemistry, 2016)
In this study, we have carried out a combined experimental and computational investigation to elucidate several bred-in-the-bone ideas standing out in rational design of novel cationic surfactants as antibacterial agents. Five 3-hydroxypyridinium salts differing in the length of N-alkyl side chain have been synthesized, analyzed by high performance liquid chromatography, tested for in vitro activity against a panel of pathogenic bacterial and fungal strains, computationally modeled in water by a SCRF B3LYP/6-311++G(d,p) method, and evaluated by a systematic QSAR analysis. Given the results of this work, the hypothesis suggesting that higher positive charge of the quaternary nitrogen should increase antimicrobial efficacy can be rejected since 3-hydroxyl group does increase the positive charge on the nitrogen but, simultaneously, it significantly derogates the antimicrobial activity by lowering the lipophilicity and by escalating the desolvation energy of the compounds in comparison with non-hydroxylated analogues. Herein, the majority of the prepared 3-hydroxylated substances showed notably lower potency than the parent pyridinium structures, although compound 8 with C12 alkyl chain proved a distinctly better antimicrobial activity in submicromolar range. Focusing on this anomaly, we have made an effort to reveal the reason of the observed activity through a molecular dynamics simulation of the interaction between the bacterial membrane and compound 8 in GROMACS software.
Keywords: Hydrophobic and Hydrophilic Interactions; Fungi; viabilita buněk; kvantitativní vztahy mezi strukturou a aktivitou; simulace molekulární dynamiky; Surfactants; hydrofobní a hydrofilní interakce; CHO Cells; antibakteriální látky; Bacteria; Molecular Dynamics Simulation; houby; Cell Survival; QSAR; Molecular modeling; molekulární konformace; Cricetulus; Molecular dynamics; Cricetinae; Antimicrobials; Animals; CHO buňky; Anti-Bacterial Agents; zvířata; Quaternary ammoniums salts; pyridiny; Pyridines; Molecular Conformation; Quantitative Structure-Activity Relationship; křečci praví